Comparison of Shoulder and Elbow Range of Motion and Arm Muscle Strength in Humerus Fractured Patients Treated with Operative and Non-operative at Dr. Soebandi Hospital - Dedy Chandra Hariyono; Muhamad Hasan; Rony Prasetyo (Journal of Agromedicine and Medical Sciences, 2015)
Humerus fracture is a disruption of normal architecture in humerus bone . This study was conducted to identify The Range Of Motion (ROM), muscle strength of arm and analyze the comparison of the ROM and muscle strength on humerus fracture patients between operative and non-operative treatment. This research used non-experimental study with cross-sectional design. Observed variables were Range of Motion and muscle strength each measured by goniometer and muscle strength scale, respectively. Comparing to these circumstances, there were significant difference in shoulder abduction, shoulder flexion, shoulder extension, elbow extension and elbow flexion between operative treatment patients and non-operative treatment patients at dr. Soebandi Hospital Jember. Keywords : humerus fracture, range of motion, muscle strength.